Doing Theology with Henri de Lubac - Kristiatmo, Thomas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
Henri de Lubac was one of the many theologians who have brought new dynamics in theology through his interpretation of the theology and the philosophy of Thomas Aquinas. This paper wants to explore his contributions to the methods of theologizing in the church. De Lubac’s interpretation of the relation between the natural and the supernatural supports the movement “Nouvelle Théologie” that appreciates the mysterious aspects of God as understood through the Christian Scriptures and traditions. According to de Lubac’s interpretations of Thomas Aquinas, the seeds of the supernatural are already present in the natural within the human beings. The author argues that hermeneutics and correlation are two important methods that underlie de Lubac’s ideas in putting the Scriptures as the main source of the theology insofar as the Scriptures are linked with human experience and reality. The return to theology is the return to the Scriptures and tradition, but this is always in relation to the human experiences and the contemporary world situations. Key Words:*Neo-scholasticism, *Nouvelle Théologie, *The natural, *The supernatural, *Ressourcement, *Nature, *Potency, *Grace, *Anagogy, *Experience, *Tradition, *Hermeneutics, *Correlation.